Marketing Strategy for Aisyah Collection Muslim Fashion in Samarinda - Nurul Istiqomah; Noor Ellyawati; Sutrisno Sutrisno (Peneliti.net, 2026)
The tight business competition in the Muslim women's fashion industry makes MSME actors need to have the right marketing strategy to survive and grow. This research aims to find out the marketing strategies applied in managing the business and most importantly used by Aisyah Collection so that it can survive to date. This study uses a descriptive qualitative approach with in-depth interview techniques with five informants who were selected purposively. The data collection instrument was in the form of semi-structured interviews with open interview guidelines. Researchers use source triangulation to test the credibility of data across multiple sources. Data analysis consists of data reduction, data presentation, and conclusions. The focus of the study is directed at four indicators of marketing strategy: product, price, venue, and promotion. The results of the study show that Aisyah Collection as an MSME that opens a business at home still uses a marketing strategy that includes products, prices, places, and promotions. In Aisyah Collection's business, the implementation of marketing strategies that are often carried out is to maintain product quality, ensure that prices remain affordable, utilize private houses as physical locations and use social media Facebook and WhatsApp as promotions so that their businesses can survive and compete in the market. Thus, product, price, place, and promotion indicators are very important for business actors in determining effective marketing strategies, increasing competitiveness, meeting consumer needs and satisfaction and reaching a wider range of potential buyers.